RANCANG BANGUN SISTEM PENDUKUNG KEPUTUSAN DALAM PENENTUAN PRESTASI KEPENGURUSAN PADA ORGANISASI KEMAHASISWAAN IBI DARMAJAYA MENGGUNAKAN METODE SAW (SIMPLE ADDITIVE WEIGHTING) - Saleh, Sushanti; Widakdo, Dika Tondo (244-5567)
Informatics and Business Institute (IBI) Darmajaya is one of the private institutes in Lampung which has some organizations called Student Organizations (ORKEM) and under the lead of Vice Rector III and the Bureau of Student and Marketing. Student organizations existing in IBI Darmajaya is 20 organizations that are divided into six departments and two high-campus institutions. With a number of organizations, it would be very difficult to give a good or bad assessment about the organization, because the criteria used only rely on the deadlines of making proposals, and gathering for reports. Decision support systems in determining student organization management achievement of the IBI Darmajaya student organizationz designed in this research is expected to provide benefits in replacing the current assessment system. The method used in this research is Simple Additive Weighting (SAW) with a weighting for each assessment criteria. The result of this research can assist in determining and selecting student organization management achievement in a period of tenure also making the  process of assessment and giving rank easier. The output result is an information in the form of rank report on the best management of student organizations in IBI Darmajaya.Keywords : Decision Support System for Determining Achievement, (Simple Additive Weghting (SAW)